Study on Electronic Properties of α-Uranium using Ab-initio Approach - Vora, Aditya M. (BIBECHANA, 2022)
In the present work, a density functional theory (DFT) based simulation is performed to study the electronic properties of (-uranium through the electronic band structure, total electron density of states (DOS), integrated density of states (IDOS), partial density of states (PDOS) and Fermi-surface measurements. A Generalized Gradient Approximation (GGA) with Projector-Augmented Wave (PAW) pseudopotential is used in present computation. The hybridization between the 5f orbital and 6d orbital also has fairly influences on the electronic Properties of α-Uranium.BIBECHANA 19 (2022) 208-213